Integrating Multicultural Perspectives in History Education under the Merdeka Curriculum: A Critical Case Study from Post-Colonial Indonesia - Adinda Dwita Putri; Romadi Romadi (Indonesian Journal of History Education, 2026)
Abstract: This study critically explores the incorporation of multicultural perspectives within history education under Indonesia's Merdeka Curriculum at SMA Negeri 1 Lasem, a school characterised by considerable ethnic and religious plurality. Employing a qualitative case-study approach, the research scrutinises teachers' conceptualisations and applications of multicultural values, along with the obstacles they encounter and students' perceptions of such learning. Findings indicate that although teachers display commitment to tolerance and inclusivity, multicultural integration remains superficial, involving tokenistic content inclusion that fails to engage with the structural and epistemological dimensions of transformative education. This superficiality is compounded by ambiguous curriculum guidelines, insufficient professional development, and persistent examination-driven teaching practices. The study contends that meaningful multicultural history education in post-colonial settings must move beyond tolerance discourse towards critical interrogation of power, narrative construction, and the epistemic foundations of historical knowledge.   Abstrak: Studi ini secara kritis mengkaji integrasi perspektif multikultural dalam pendidikan sejarah di bawah Kurikulum Merdeka di SMA Negeri 1 Lasem, sekolah dengan keragaman etnis dan agama signifikan. Menggunakan pendekatan studi kasus kualitatif, penelitian menelaah konseptualisasi dan penerapan nilai multikultural oleh guru, hambatan yang dihadapi, dan persepsi siswa. Temuan menunjukkan bahwa meski guru berkomitmen pada toleransi, integrasi multikultural masih dangkal, menyertakan konten simbolis tanpa menyentuh dimensi struktural dan epistemologis pendidikan transformatif. Kedangkalan diperparah oleh pedoman kurikulum ambigu, kurangnya pengembangan profesional, dan praktik pengajaran berorientasi ujian. Studi ini menyimpulkan bahwa pendidikan sejarah multikultural yang bermakna di konteks pascakolonial harus melampaui wacana toleransi menuju telaah kritis kekuasaan, konstruksi narasi, dan fondasi epistemik sejarah.